2006
DOI: 10.7888/juoeh.28.401
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Gram-Positive Spore-Forming Bacteria Including <i>Bacillus cereus</i> after Hand Washing Using Alcohol-Based Handrub

Abstract: Hand washing is the most fundamental method for preventing infection. Currently, hand washing with an alcohol-based handrub is the international gold standard method. However, in our study we found many samples of ineffective hand washing using an alcohol-based handrub. The rates of ineffective samples were 10.4% (5/48) in 2004 and 34.3% (12/35) in 2005. We examined the morphology by Gram staining and biochemical properties of the bacteria which remained after hand washing in 2005. Their colonies were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[63] The results of this study indicated that use of this antiseptic for 1 year has reduced its antimicrobial activity to two-thirds. Another study results showed that based on coliform count after contact with animals had increased.…”
Section: Discussionmentioning
confidence: 96%
“…[63] The results of this study indicated that use of this antiseptic for 1 year has reduced its antimicrobial activity to two-thirds. Another study results showed that based on coliform count after contact with animals had increased.…”
Section: Discussionmentioning
confidence: 96%